PENGETAHUAN LOKAL TENTANG TUMBUHAN SEBAGAI SUMBER PANGAN OLEH MASYARAKAT SUKU ANAK DALAM (Studi Pada Masyarakat Suku Anak Dalam di Kawasan Taman Nasional Bukit Duabelas Kabupaten Sarolangun) - Nining Nuraida (Jurnal Biotek, 2019)
The people of Suku Anak Dalam (SAD) who lived in Taman Nasional Bukit Duabelas district, fulfill their needs using the natural resources around the district. This research intended to reviewing the local people of SAD’s knowledgein using plants as their food resources and using plants as their food resources and getting information about variety of platns which are using as their food resources. This research is qualitative. Data collection used pasif participatory observation, half structured interview, and documentation. Based on the result of the research, it is stated that the people of Suku Anak Dalam have a high level of knowledge about plants as food resources. Interaction factor with the nature and environment produced the wisdom in management of natural resources to be useful continuosly and hereditary. There are 41 variety of plants including 10 kinds of food reseorces, 1 kind of  vegetabes and 31 kinds of fruits.